แนวทางการสร้างความจงรักภักดีต่อการท่องเที่ยวเชิงอาหารของประเทศไทยผ่านคุณค่าเชิงประสบการณ์ - อนันต์ กฤติเดช; สุกเพชร เกศรา (Thai Journal of Science and Technology, 2019)
Abstract This research is a quantitative research to study factors and the proposed ways to create loyalty guidelines for culinary tourism in Thailand through experiential value. Data were collected from the target samples (400 European tourists traveling to Thailand those were interested in Thai food or participated in Thai food activities at least 1 time per trip), by using questionnaires. The results of simple and multiple regression analyses showed that experiential value influences the loyalty of culinary tourists in Thailand. The consumer return on investment (CROI) has the highest positive influence. Therefore, the guidelines for creating loyalty to culinary tourism in Thailand through experiential value are aimed at creating the most effective of CROI factors. Suggestions from this research study are followings; (1) government agencies or agencies in the tourism industry of Thailand should make standards to control the price of Thai food sold to foreign tourists fairly for creating a positive image of Thai food, (2) agencies related to tourism promotion should aim to promote the image of Thai food that is creative with a memorable feeling, (3) private sector, restaurant operators should develop cleanliness and neatness of restaurants and employees, and (4) education sector can apply the guidelines to create experiential values for future studies especially the CROI factors creating. Keywords: loyalty; culinary tourism; experiential value